The Optimal Design of the Qianhai Special Economic Zone - Bryane Michael; Naubahar Sharif; Seung-Ho Park (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Qianhai – an innovation park in Shenzhen – has the possibility of boosting innovation in Hong Kong, Shenzhen and in the wider region. This paper analyses the costs and benefits of existing plans for Qianhai and discusses the profit-maximising design of the Qianhai. We review existing evidence about which policies have promoted profitable innovation in the Qianhai region (Hong Kong and Shenzhen) in the past. We also show how a raft of legal changes concomitant with Hong Kong-Shenzhen development of Qianhai can increase innovation-led profits in the two jurisdictions. Some of these changes touch upon the mandate and organisation of the Qianhai Authority itself, and relatively poor-performing innovation agencies and schemes especially in Hong Kong. We find that such a zone would increase innovation-led profits in the logistics, IT, and other Qianhai-targeted sectors by a factor of four in the short-run and a factor of ten in the longer run. As a contribution to the wider field of innovation policy, we derive a model of the optimal innovation agency. That model shows the equilibrium and optimal levels of profits, R&D spending and cash/investment for innovative companies in a particular jurisdiction.
Keywords: P48; R12; R58; 330; Qianhai; Cross-border economic zones; innovation; special economic zones